MENELADANI NILAI AJARAN DAKWAH SUNAN KALIJAGA DALAM MENDIDIK KARAKTER BANGSA DI ERA GLOBALISAS - Hermawan, Agus (ATTARBIYAH, 2016)
This article describes moral value based on Sunan Kalijagaâs perspective, one of the members of the walisanga who had the longest age from other wali and he was the most famous and creative wali in creating a wide range of media to preach Islam. The media that he made and applied included many fields; such as preacher, literatures and songs (Ilir-ilir song, gundul-gundul pacul, and dandang gula song), Sculpture, Gamelan, mosques, Tatal and Kenthong art, Bedhug, and Â grebeg sekaten contained character of education that were stil relevant applied in this era. Thus, a preacherâs function as learning model takes strategic position in preparing and applying any media and approaches/ strategy to lead students to be success in their learning. The media of learning to preach created by Sunan Kalijaga were the collaboration between culture of local wisdom which was maintained and elements of modern constructive art that was relevant with the local wisdom.